Jornada laboral no contexto bancário: efeitos na organização do trabalho em cargos de gestão - Gomes, Victoria de Vasconcelos (2024)
Work scale-up in banking is grounded on transforming productive processes to meet the financial market’s increasing demands. We witness substantial workforce cutbacks in this job market and some measures that aim to minimize costs, characterized by: 1) increased outsourcing; 2) implementation and intensive use of new information technologies; and 3) incorporation of a management model to maximize financial results. The intensified automation and implementation of new technologies reconfigure work. Technical and specialized activities have given way to more general tasks, emphasizing the sale of services and financial products, a productive restructuring reverberating today. Given this situation, we recognize the change in the work setting in financial institutions. Hence, we aim to investigate the effects of working hours on the organization of banking work in management positions. This qualitative study’s objective is highlighting how working hours influence the experience and organization of time grounded on the workers’ discourse. The research was divided into two stages: a) the first stage applied an online questionnaire through Google Forms; and b) the second stage held interviews with the staff who agreed to go to this stage of the study, where each stage of the research had 25 and 5 participants, respectively. The interviews were in-person or online through a formal invitation or applying the “snowball” technique. Data analysis and construction was undertaken using Bardin Content Analysis, using Thematic/Categorical Analysis as the main technique for identifying themes that relate to our research objective. The investigation brings as results some reverberations for us to think about how the pressure for results, excess productivity, qualification courses and technological advances that make disconnection difficult, end up invading the lives of bank managers in other dimensions that no longer correspond to the dimension of work, but which are substantially determined by it.